Managing innovation - Tidd, Joseph,Bessant, John R. (Wiley, 2021)
Now in its seventh edition, Managing Innovation: Integrating Technological, Market and Organizational Change enables graduate and undergraduate students to develop the unique skill set and the foundational knowledge required to successfully manage innovation, technology, and new product development. This bestselling text has been fully updated with new data, new methods, and new concepts while still retaining its holistic approach the subject. The text provides an integrated, evidence-based methodology to innovation management that is supported by the latest academic research and the authors' extensive experience in real-world management practice.Students are provided with an impressive range of learning tools–including numerous case studies, illustrative examples, discussions questions, and key information boxes–to help them explore the innovation process and its relation to the markets, technology, and the organization.
9781119713302
Keywords: Change Management; Literatur für Manager; Betriebswirtschaft; Business & Management; Business & Management Special Topics; Spezialthemen Wirtschaft u. Management; Wirtschaft; Wirtschaft u. Management; Strategisches Management; Markt; Technischer Fortschritt; Innovationsmanagement; Integriertes Management; Management; Technische Innovation; Marktentwicklung; Organisationswandel; Innovation